How regional blocs affect excluded countries : the price effect of MERCOSUR - Chang, Won (2002)
Examines the effect of MERCOSUR on the prices of its imports from nonmembers. Focuses on the Brazilian import market since it is large and Brazil is the largest country in MERCOSUR. Discovers that the creation of MERCOSUR was associated with significant declines in the prices of nonmembers' exports to the region.